Architecture of a quantum computing platform. (February 2019) - Ismagilov, Marat; Sayfutdinov, Rustam; Vasiliev, Alexander
Abstract: We present an architecture of a cloud-based quantum computing platform. It is based on the original model of a nanophotonic quantum processor with integrated quantum memory and a quantum transistor. At the moment the platform works with an integrated quantum simulator that implements the behavior of the underlying model.